2001
DOI: 10.1038/sj.jea.7500145
|View full text |Cite
|
Sign up to set email alerts
|

Household appliance use and residential exposure to 60-Hz magnetic fields

Abstract: We characterized the distribution of exposure to magnetic fields ( MFs ) during daily activities and during household appliance use, and estimated the relative contribution of various activities and appliances to total daily exposure. One hundred sixty -two subjects provided information on their patterns of appliance use and wore personal monitors for 24 h to collect MF exposure data. Of total exposure, 27% accumulated while subjects were in bed; 41% while at home but not in bed; 9% at work; and 24% elsewhere.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…In general, the exposure reported refers to sources such as VDUs, which are not usually recognized as important sources of high-intensity exposure to EMFs (35,36). However, the importance of computer use on personal exposure to 60-Hz magnetic fields when considering 24-hr exposure was recently demonstrated (37). Most of the controlled studies did not evaluate the effect of different kinds of exposure to EMFs (e.g., varying frequency, intensity and time course of exposure) but instead focused on a simple exposure setting corresponding to what was usually reported by patients.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the exposure reported refers to sources such as VDUs, which are not usually recognized as important sources of high-intensity exposure to EMFs (35,36). However, the importance of computer use on personal exposure to 60-Hz magnetic fields when considering 24-hr exposure was recently demonstrated (37). Most of the controlled studies did not evaluate the effect of different kinds of exposure to EMFs (e.g., varying frequency, intensity and time course of exposure) but instead focused on a simple exposure setting corresponding to what was usually reported by patients.…”
Section: Discussionmentioning
confidence: 99%
“…The low capability of predicting 72-h ELF magnetic filed by the regression model was likely owing to lack of consideration of some other vital sources of indoor ELF magnetic field. Many studies have empirically demonstrated that a number of factors including loads on external power lines , electrical wiring in residential areas (Moriyama and Yoshitomi, 2005), residence age (Kavet et al, 1999), ground current and service loops (Kavet et al, 1999), and the use of domestic appliances (Mezei et al, 2001) are associated indoor ELF magnetic filed. Although previous studies demonstrated that high voltage transmission lines alone may contribute dominantly and substantially to the residential ELF magnetic filed (Levallois et al, 1995;The´riault and Li, 1997) at home close to the line, and that measured ELF magnetic field correlated well with the calculated field for residences within 50 m away from hightension power lines (The´riault and , the findings from this study indicated that consideration of high-tension power lines alone might be far from sufficient to predict residential exposure to 72-h ELF magnetic fields even in households very close to high-tension power lines.…”
Section: Discussionmentioning
confidence: 99%
“…Data on adult cancer and residential exposure to ELF EMF, including the use of appliances, are sparse and methodologically limited (56,84). Because earlier evidence suggested that residential exposure is not a risk factor for adult cancers and because researchers expected that occupational studies would provide a more powerful test of adult cancer hypotheses than would residential ones, studies using the next generation of residential exposure assessment methods, such as long-term measurements and calculated fields, focused on children.…”
Section: Cancermentioning
confidence: 99%
“…Several studies of the relationship between electrical appliance use and various childhood cancers have been published (56,76). In general, these studies provide no discernable pattern of increased risk associated with increased duration and frequency of appliance use.…”
Section: Effects In Childrenmentioning
confidence: 99%